دور التغطيـــة في تحسيـــن أداء الشبكــــات الخلويــــــة - حسن عباس; كنان علي غانم (Tishreen University, 2019)
يعرض هذا البحــث المحددات الرئيسية المستخدمة من أجل تأمين تغطية شاملة في الشبكات الخلوية بهدف تأمين وثوقية النظام ونوعية خدمات جيدة كما يدرس العوامل المؤثرة في تحسين التغطية مما ينعكس على الأداء العام للشبكات الخلوية الأمر الذي يمكن جميع المشتركين من استخدام خدمات هذه الشبكات بسهولة ويسر فعندما نتحدث عن أداء الشبكات الخلوية فإن أول ما يتبادر إلى ذهننا هو التغطية التي تعتبر البوابة الرئيسية التي تدخل من خلالها جميع الخدمات وصولاً إلى المشتركين الذين يتصلون ويتحركون..  . كما يهدف هذا البحث يهدف إلى دراسة التغطية كركن أساسي من أركان النظام في شبكات الاتصال الخلوي، بهدف الوصول إلى نظام أكثر وثوقية ونوعية. ويعرض هذا البحث دور العوامل التي تتحكم بفعالية ومدى التغطية ومدى تأثيرها، آخذين بعين الاعتبار كل الظروف بدءاً من حالة التغطية المبدئية وصولا إلى التغطية الشمولية التي تسعى جميع الشركات المشغلة إلى تحقيقها بسرعة قياسية وبكلف استثمارية قليلة. وأخيرا يتضمن البحث قياسات حية لبارامترات الإشارة الخلوية للشبكة الخلوية السورية واحصائيات تعكس الأداء الفعلي  للشبكة المحلية  حيث قمنا بتسجيل القياسات في مراحل مختلفة من تطوير الشبكة على مدى عدة أشهر  بالتعاون  مع الشركتين المشغلتين. This research explains the main parameters used to provide a complete coverage in cell phone networks in order to provide a system reliability and better services quality.  It also studied the factors that help to improve the coverage the thing that affects the general performance of the networks, and enables all subscribers use the services of these networks easily. The first thing comes to mind when talking about the networks is coverage which is considered the main gate through which all services pass, reaching the subscribers who communicate and move. This research also aims studying the coverage as a basic element in the cell-phone communication system in order to get a more reliable, with high quality system. It also illustrates the role and the effects of the factors that control the efficiency and the range of the coverage taking into consideration all the circumstances starting from the primary coverage till reaching a full coverage, the thing that all the operating companies aim to achieve in a high speed with less investment costs. The research also includes live measurements of the cell phone sign parameters of the Syrian network, besides statistics that reflect the true performance of the local network. There are also records of the measurements in the different phases of the development of the network in a range of a few months with the cooperating of the two operating companies in Syria.